The Effectiveness of COW through the AI Writing Assistant Platform: Moderating Self-Efficacy and Digital Literacy in English Language - Firlia Nurul Anisa; Mohammad Sofyan Adi Pranata (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Writing skills are essential in English as a Foreign Language (EFL) learning, yet many high school students experience difficulties in generating ideas, organizing texts, and revising their writing effectively. Integrating Artificial Intelligence (AI) Writing Assistants with Collaborative Online Writing (COW) offers a promising approach to enhancing writing performance through collaborative and process-oriented learning. This study investigates the effectiveness of AI-assisted COW in improving students' English writing skills, with self-efficacy and digital literacy examined as moderating variables. A quantitative approach employing a quasi-experimental non-equivalent control group design was adopted. Participants consisted of eleventh-grade public high school students assigned to experimental and control groups. Data were collected through pre- and post-writing tests, self-efficacy questionnaires, and digital literacy questionnaires, then analyzed using inferential statistics and moderation regression analysis. The results revealed that students receiving AI-assisted COW achieved significantly greater improvements in writing skills than those in the control group, with a substantial effect size. Moreover, self-efficacy and digital literacy significantly strengthened the positive relationship between AI-assisted COW and writing achievement, indicating that students with higher levels of both variables gained greater learning benefits. These findings demonstrate that integrating collaborative online writing with AI technology effectively enhances EFL students' writing skills while highlighting the importance of fostering self-efficacy and digital literacy to maximize learning outcomes.